Antidiabetic effect of actinodaphne angustifolia and profiling of bioactive metabolites using UPLC-QToF/ESI-MS method - F, Md. Shaekh; WI, Wan Maznah; MA, Mohd Fadhlizil Fasihi; A, Shihab Uddin; R, Kamrul; T, Saiful Nizam; H, Akm Moyeenul (Penerbit Universiti Kebangsaan Malaysia, 2023)
Diabetes mellitus is a chronic disorder that causes elevated blood glucose levels due to a lack of insulin, either completely or partially. We investigated the antidiabetic property of Actinodaphne angustifolia in a rat model and identified the bioactive phytochemicals by using the UPLC-QTOF/ESI-MS method. The rats’ pancreatic structures, lipid profile and blood glucose were assessed after a one-week intervention. UPLC-QTOF/ESI-MS analysis was conducted to identify flavonoids and terpenoids in the leaf extract. Actinodaphne angustifolia extract markedly increased the high-density lipoprotein (HDL) (p<0.05) while reducing total cholesterol (TC), low-density lipoprotein (LDL) and blood glucose. Furthermore, the tissue architecture of pancreatic islets was also well recovered as compared to the control group. A total of 45 flavonoids and 109 terpenoid compounds were identified using UPLC-QTOF/ESI-MS-based analysis and additional studies should be undertaken to identify the potential antidiabetic agents.